STUDI TENTANG KESULITAN BELAJAR GEOGRAI SISWA DI SMA NEGERI I SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - Sageileppak, Julesdi; Suarto, Edi; Yuherman, Yuherman (Pendidikan Geografi, 2013)
Â This study aimed to obtain information, analyze about Learning Difficulties in SMA 1 Siberut Selatan Mentawai Islands regency views of : 1 ) Learning Difficulties in SMA 1 Siberut Selatan Mentawai Islands and ( 2 ) the efforts made to overcome learning difficulties in SMA 1 Siberut Selatan Mentawai Islands.The subjects were students of SMA 1 Siberut Selatan Mentawai Islands. Reason for the selection of research subjects because the class there are many students who have learning difficulties . As informants in this study were students of SMA 1 Siberut Selatan Mentawai Islands. Data analysis was performed through data reduction, data display and conclusion.Research results showed: ( 1 ) difficulty in learning geography student at SMA 1 Siberut Selatan Mentawai Islands stemming from internal factors is the understanding that students are still lacking in geography lessons , psychological factors such as attention to the subject , lack of motivation and lack of parental readiness of students to learn and external factors are factors that are less family support student learning and teacher factors that are less able to convey the material and ( 2 ) the efforts of the students to overcome difficulties in learning Geography is well prepared when going to learn , maintain health , set the time to learn it well, understand the subject matter and do not forget to give understanding to parents the importance of learning at home so that parents support when students learn at home